Entrevue guidée avec Marie-Claire Carpentier-Roy - Daniel Drolet; Esther Cloutier; Raymond Baril (Perspectives Interdisciplinaires sur le Travail et la Santé)
Trained as a sociologist, and cofounder of the Québec occupational psychodynamics network, Marie-Claire Carpentier-Roy has a passion for research and fieldwork. During her career, she knew how to bring out in the open the issues related to subjectivity and its effects on mental health. She is a keen researcher with impeccable integrity, and for her, mental health is more than a subject for study, it is a mission. PISTES met with her as she was preparing for her retirement.